Feasibility and mid-term results of transcatheter pulmonary valve replacement using Edwards-Sapien valves. (3rd October 2022) - Calvo-Barcelo, M; Belahnech-Pujol, Y; Betrian-Blasco, P; Dos-Subira, L; Pijuan-Domenech, A; Giralt-Garcia, G; Miranda-Barrio, B; Gordon-Ramirez, B; Gonzalez-Fernandez, V; Rodenas-Alesina, E; Roses-Noguer, F; Garcia-Del Blanco, B; et al.
Abstract: Background: Transcatheter pulmonary valve replacement (TPVR) is an alternative to surgery in certain patients with pulmonary valve dysfunction. When feasible, a percutaneous approach is increasingly common in congenital heart disease (CHD). There is paucity of data to support the use of the Edwards Sapien (ES) 3 or XT valves for TPVR. Purpose: To describe the feasibility and outcomes of TPVR with the ES valve. Methods: Consecutive patients who underwent TPVR between 2014 and 2021 in a tertiary referral center for CHD were retrospectively included. Outcomes assessed included complications during admission, echocardiographic parameters of ventricular remodeling after TPVR as well as mortality and valve-related complications during follow-up. Results: During the study period, 70 patients underwent TPVR with the ES valve. Of them, 70% were men with a median age of 28.3 years. The underlying cardiac conditions were tetralogy of Fallot (N=35, 45.7%), pulmonary atresia or stenosis with ventricular septal defect (N=10, 14.3%), pulmonary stenosis (N=10, 14.3%) and Ross procedure (N=5, 7.1%). The main reason for TPVR was pulmonary regurgitation (N=23, 33.3%), pulmonary stenosis (N=10, 24.6%) or a combination of both (N=29, 42.0%). Transfemoral access (N=68, 97.1%) was more common than transjugular (N=2, 2.9%). TPVR was performed in a native or patch-extended right ventricular outflow tract (N=26, 37.1%), as a valve-in-valve procedure in a previous bioprosthetic valve (N=23, 32.9%) or within a conduit (N=21, 30.0%: 11 homografts, 9 heterografts and 1 Dacron conduit), and stenting before deploying the valve was performed in 48 (68.5%) cases. TPVR was successful in 69 (98.6%) patients with iatrogenic tricuspid damage in 2 cases, with a median hospital length of stay of 1 day, no deaths and 4 serious complications during admission (2 pulmonary edema, 1 femoral vein rupture and 1 pulmonary bleeding). Urgent surgery was not required in any case. No cardiovascular deaths, pulmonary thromboembolisms or strokes were observed during a median follow-up 25.9 months. During this period, there was 1 non-cardiac death, 1 heart transplant, 3 endocarditis (without valve dysfunction), 1 prosthetic valve degeneration and 1 subclinical prosthetic thrombosis. After 1 year, the mean echocardiographic transprosthetic peak gradient was 23 mmHg and there was a reduction in the number of patients presenting moderate-to-severe tricuspid regurgitation (22.9 to 14.8%). Conclusions: TPVR with ES valves is feasible and safe in a variety of substrates and ACHD population, with a short length of stay and a low rate of adverse events both in the medium-term follow-up. Funding Acknowledgement: Type of funding sources: None.